International Ski Federation
Homepage des Internationalen Skivsporterband FIS. Content: News, event calendar and results, FIS points and standings, competitors, rules and publications, inside FIS, mediaworld, sponsors, member service, links for cross country skiing, ski jumping nordic combination, alpine skiing, freestyle, snowboarding.